PELAKSANAAN PERATURAN MENTERI PERHUBUNGAN REPUBLIK INDONESIA NOMOR PM 118 TAHUN 2018 TENTANG PENYELENGGARAAN ANGKUTAN SEWA KHUSUS (Studi Kasus pada Taksi Online di Kota Yogyakarta) - GEMILAR, ANTONIUS (Dinamika Hukum, 2019)
The purpose of this research is to study and analyze the implementation of regulation of the Minister of Transportation of the Republic of Indonesia number PM 118 year 2018 about the implementation of special rental transportation in the online taxi of Yogyakarta. Reviewing and analyzing the implications of implementing regulation of the Minister of Transportation Republic of Indonesia number PM 118 year 2018 about the implementation of special rental transportation in online taxis in Yogyakarta city. The method of approach in writing is sociological juridical. The specification of this research uses analytical descriptive. Data sources use primary data and skunder data. Data collection techniques using interview and observation studies. To analyze the data, researchers use qualitative descriptive analysis methods. Based on the results of the study obtained the conclusion of the implementation of regulation of the Minister of Transportation Republic of Indonesia number PM 118 year 2018 about the implementation of special rental transportation in the online taxi city Yogyakarta has not been implemented optimally is shown by not all online taxis are legal entities both limited and cooperative company, this is due to the process of licensing cooperative establishment or PT takes a long time. The implications of the implementation of PM 118 year 2018 on the implementation of special rental transportation in online taxis in the city of Yogyakarta, which is the application company does not carry direct transportation in the field of transport but should cooperate with Transport companies. Reviewed from the legal theory of implementation of PM 118 year 2018 on the substance aspect already set about suspend, set the problem of Minimal service standards (SPM) aimed at the driver and passengers get service and protection, regulate Regarding the lower tariff limit and upper tariff limit, the organizer of special rental transportation must be legal entity, both state enterprises, BUMD, PT, cooperatives and in the form of SMES. The aspect of the legal structure of the Department of Transportation has the authority to issue the operational license of special rental transport and the applicator company Gojek and Grab have a role to coordinate with the transportation office to take care of the permits. Aspects of the legal culture show still the violation of the applicator company and online taxi drivers. The applicator company's breach does not constitute the provision that a prospective online taxi driver must have a member card in the company or cooperative, while the online taxi driver has not implemented the minimum standards of service is set in PM 118 year 2018 and the driver's identity does not match the one in the application. Keywords: policy implementation, maintenance of special rental transport.